2016
DOI: 10.17796/1053-4628-40.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Filling after Revascularization/Revitalization

Abstract: This case demonstrates that once the increased thickening of the canal walls, incrementing the root length, apical closure and the total resolution of the apical lesion are observed, the main canal of a previously treated tooth with an RR procedure can be filled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…LGP Santos et al presented color change (8-11,73-75, 80,81). Considering the 63 teeth treated with AM to TAP/AM to GMTA, 21 (33.3%) presented crown discoloration (6,7,13,14,69,70,72,(76)(77)(78)(79). Thus, a tendency to avoid dental color alterations in studies that employed alternative materials (to TAP and GMTA) is observed in the Figure 2.…”
Section: Synthesis Of Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…LGP Santos et al presented color change (8-11,73-75, 80,81). Considering the 63 teeth treated with AM to TAP/AM to GMTA, 21 (33.3%) presented crown discoloration (6,7,13,14,69,70,72,(76)(77)(78)(79). Thus, a tendency to avoid dental color alterations in studies that employed alternative materials (to TAP and GMTA) is observed in the Figure 2.…”
Section: Synthesis Of Resultsmentioning
confidence: 98%
“…A reduced number of cases reporting discoloration were observed when Ca(OH) 2 was applied as intracanal medication, however, from 20 teeth revascularized with Ca(OH) 2 six presented some color change (14,69,(76)(77)(78)(79)(80)(81). This may be explained by the fact that the materials used in the cervical plug can also promote discoloration, especially GMTA (80,81).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations